Corrosion properties of ceramic coating on pure titanium by pack boronizing with Nd2O3. Issue 10 (15th May 2023) - Feng, Zhiqi; Duan, Yonghua; Cao, Yong; Qi, Huarong; Peng, Mingjun; Wang, Xiaoqi
Abstract: In this work, the corrosion behaviors and mechanisms of the pure titanium by pack boronizing with different Nd2 O3 contents in 3.5 wt% NaCl and 5.0 vol% H2 SO4 solutions were characterized and analyzed by scanning electron microscope (SEM), X-ray diffraction (XRD), X-Ray photoelectron spectroscopy (XPS), electron probe microanalyzer (EPMA), and electrochemical tests. The results showed that the sample boronized with 4 wt% Nd2 O3 has the smoothest surface, the densest ceramic coating with a thickness of 52 μm, and the best corrosion resistance. Nd2 O3 can react with B to generate Nd–B active group, which promotes ceramic coating growth and turns local corrosion into uniform corrosion.